Cytotaxonomical remarks on Allium serbicum (Amaryllidaceae), a misappreciated species of the Balkan flora - Bogdanović, Sandro; Anačkov, Goran; Salmeri, Cristina; Galdo, Gianpietro Giusso Del; Brullo, Salvatore (Phytotaxa, 2024)
Allium serbicum is a critical and unappreciated species described from Serbia (Balkan Peninsula), and usually treated as a synonym of A. pallens or A. tenuiflorum. Based on living and herbarium material it was possible to clarify its morphology, karyology, leaf anatomy, pollen grain and seed testa microsculpturing, ecology and chorology of this very peculiar and rare endemic species. It is diploid with 2n = 16 chromosomes, and seems taxonomically quite isolated, since it is morphologically well differentiated from the other species of A. sect. Codonoprasum, with very specialized ecological requirements, being a glareicolous plant localized exclusively on calcareous screes. In addition, a second-step lectotypification, a detailed description, a new iconography, distribution map and conservation status are also provided.